How Does the Digital Economy Influence the Pursuit of Sustainable Development Goals? - Moussa, Wajdi; Mgadmi, Nidhal; Guachaoui, Afef; Regaïeg, Rym (Journal of Telecommunications and the Digital Economy, 2024)
Our study aims to examine the impact of the digital economy on sustainable development during international financial crises, the COVID-19 pandemic, and the current war between Russia and Ukraine. To do this, we collected an annual dataset from 1990 to 2022 for twenty-eight developed and twenty-five developing countries, to identify links between environmental, socio-economic, and proxy indicators of the digital economy. We estimate these links using the Within and GLS methods and use the Hausman (1978) test for individual effects to determine the nature of these links. Our results show that the digital economy has made a positive and significant contribution to sustainable development. For developing countries, mobile technologies have positive and significant effects on sustainable development, whereas, in developed countries, these effects are less elastic. The Internet has a positive and significant effect on the Human Development Index. While trade openness plays a driving role in environmental performance, it has a negative impact on equitable and sustainable development.